PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSET (ROA) TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN JASA KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Dini Arifian; Noviana Anggraeni; Furniawan Furniawan (Universitas La Tansa Mashiro, 2020)
This research is to find out the factors that influence bond rating through Debt to Equity Ratio (DER) and Return On Assets (ROA) ratios on financial services companies listed on the Indonesia Stock Exchange in 2015-2018. The method used in this research is a quantitative descriptive research method, the sampling technique used is purposive sampling, the method of determining respondents to be sampled based on criteria. The sample in this study consisted of 8 financial services companies ranked by PT.Pefindo and listed on the Indonesia Stock Exchange. Data collection is done by downloading financial statement data through the websites www.idx.com and www.pefindo.com.Testing of this study was carried out using the classic assumption test, then analyzed by multiple linear regression tests, correlation tests, analysis of the coefficient of determination (R2) and hypothesis testing. Using the IBM SPSS (Statistics Program For Social Science) program v.20.